2015
DOI: 10.1002/hed.24087
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical predictors in squamous cell carcinoma of the tongue and floor of the mouth

Abstract: It seems that targeting MMP-2 and VEGF-C may improve local control, thereby reducing the risk of distant metastasis in patients with SCC of the tongue and FOM. © 2015 Wiley Periodicals, Inc. Head Neck 38: E747-E753, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Of these, 118 full‐text studies were assessed, of which 68 did not meet the inclusion criteria (Appendix 2). Therefore, 50 analytical cross‐sectional studies were included in the qualitative synthesis and 15 in the quantitative synthesis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 118 full‐text studies were assessed, of which 68 did not meet the inclusion criteria (Appendix 2). Therefore, 50 analytical cross‐sectional studies were included in the qualitative synthesis and 15 in the quantitative synthesis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported the association between MMPs expression and LNM, of which nine did not present crude data, and one performed an adjusted analysis for confounding factors, although the variables used in the multivariate analysis were not stated . In addition, only four studies reported data on the association of MMPs expression with DM …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have proposed MMP2 as a prognostic biomarker for OCSCC, but all had important limitations, such as the absence of multivariate analysis (21), (22), (23), the inclusion of heterogeneous head and neck cancer patients with different tumor locations and treatments (24), (25), or retrospective cohorts with less than 60 patients (22), (23), (26), (27). Most of these studies quantified MMP2 by immunohistochemistry (IHC) through semi-quantitative methods.…”
Section: Discussionmentioning
confidence: 99%